2015
DOI: 10.1002/advs.201500057
|View full text |Cite
|
Sign up to set email alerts
|

Type I Clathrates as Novel Silicon Anodes: An Electrochemical and Structural Investigation

Abstract: Silicon clathrates contain cage‐like structures that can encapsulate various guest atoms or molecules. An electrochemical evaluation of type I silicon clathrates based on Ba8AlySi46−y as the anode material for lithium‐ion batteries is presented here. Postcycling characterization with nuclear magnetic resonance and X‐ray diffraction shows no discernible structural or volume changes even after electrochemical insertion of 44 Li (≈1 Li/Si) into the clathrate structure. The observed properties are in stark contras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
40
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 63 publications
(140 reference statements)
6
40
2
Order By: Relevance
“…Once Li ions are inserted, the electronic conductivity of LixCySi46-y is likely to increase with increasing number of Li ions inserted; subsequently, the lithiated CySi46-y clathrate may become a metal-like conductor when 8 or more Li ions are inserted [24]. Recent works by Li et al [29] and Chan et al [30,31] have shown that lithiation of BaxAlySi46-y and empty Si46 clathrates are feasible even in the presence of Ba atoms occupying some of the sites within the cage structure of BaxAlySi46-y. Thus, it is possible that some of CySi46-y clathrates doped with the alkaline metals (Na, K) or alkaline earth metals (Ba, Ca, Mg) may be lithiated and serve as potential electrode materials for Li-ion batteries.…”
Section: Hybrid Carbon-silicon Clathrates As Electronic or Electrode mentioning
confidence: 99%
“…Once Li ions are inserted, the electronic conductivity of LixCySi46-y is likely to increase with increasing number of Li ions inserted; subsequently, the lithiated CySi46-y clathrate may become a metal-like conductor when 8 or more Li ions are inserted [24]. Recent works by Li et al [29] and Chan et al [30,31] have shown that lithiation of BaxAlySi46-y and empty Si46 clathrates are feasible even in the presence of Ba atoms occupying some of the sites within the cage structure of BaxAlySi46-y. Thus, it is possible that some of CySi46-y clathrates doped with the alkaline metals (Na, K) or alkaline earth metals (Ba, Ca, Mg) may be lithiated and serve as potential electrode materials for Li-ion batteries.…”
Section: Hybrid Carbon-silicon Clathrates As Electronic or Electrode mentioning
confidence: 99%
“…Recently, the intercalation of Li‐ions into the unique, cage‐like structures of silicon clathrates was proposed as a possible option that allows for lithium storage without detrimental structural changes . It was demonstrated that the utilization of type I silicon clathrates in the form of Ba 8 Al y Si 46‐y (8<y<12) as the anode in LIBs is a feasible strategy to obtain highly reversible capacities (up to 499 mAh g −1 ) without discernible structural changes or volume expansion . In the same study, variations of the electrolyte environment already underlined that the nature of the solid electrolyte interphase (SEI) is highly impacting on the performance of the respective battery in terms of irreversible capacity loss and long term capacity retention.…”
Section: Introductionmentioning
confidence: 99%
“…In the same study, variations of the electrolyte environment already underlined that the nature of the solid electrolyte interphase (SEI) is highly impacting on the performance of the respective battery in terms of irreversible capacity loss and long term capacity retention. In this context, capacities differing by a factor of almost two were obtained after 20 charge/discharge cycles, an observation which was partially attributed to differences in insulating properties, thickness and stability of the SEI . Further studies were conducted on Ba 8 Al y Si 46‐y (y≈16, i. e. Ba 8 Al 16 Si 30 ) investigating the effect of ball‐milling and chemical etching on the surface properties and electrochemical behavior of the clathrate.…”
Section: Introductionmentioning
confidence: 99%
“…Once Li ions are inserted, the electronic conductivity of Li x C y Si 46-y is likely to increase with an increasing number of Li ions inserted; subsequently, the lithiated C y Si 46-y clathrate may become a metal-like conductor when 8 or more Li ions are inserted [24]. Recent work by Li et al [29] and Chan et al [30,31] have shown that lithiation of Ba x Al y Si 46-y and empty Si 46 clathrates are feasible even in the presence of Ba atoms occupying some of the sites within the cage structure of Ba x Al y Si 46-y . Thus, it is possible that some of the C y Si 46-y clathrates doped with the alkaline metals (Na, K) or alkaline earth metals (Ba, Ca, Mg) may be lithiated and serve as potential electrode materials for Li-ion batteries.…”
Section: Hybrid Carbon-nitrogen Clathrates As Hard Materialsmentioning
confidence: 99%
“…Recent work by Li et al [29] and Chan et al [30,31] have shown that lithiation of BaxAlySi46-y and empty Si46 clathrates are feasible even in the presence of Ba atoms occupying some of the sites within the cage structure of BaxAlySi46-y. Thus, it is possible that some of the CySi46-y clathrates doped with the alkaline metals (Na, K) or alkaline earth metals (Ba, Ca, Mg) may be lithiated and serve as potential electrode materials for Li-ion batteries.…”
Section: Hybrid Carbon-silicon Clathrates As Electronic or Electrode mentioning
confidence: 99%